Validation of the Gait Disorientation Test in children with concussion - Alkathiry, Abdulaziz A.; Alsubaie, Saud F.; Alsalaheen, Bara A.; Whitney, Susan L. (Frontiers in Pediatrics, 2022)
Background: Concussion is a complex injury that is difficult to diagnose and to assess. There are negative impacts on cognition, balance, and mobility after concussion. The Gait Disorientation Test (GDT) is an objective measure that assesses a person's balance ability by comparing the walking time with eyes open and the walking time with eyes closed in a standardized walking task. The purpose of this study was to assess the validity and the diagnostic properties of the Gait Disorientation Test (GDT) in children with concussion. Methods: Thirty-six children with concussion and ninety-one controls aged between 9-18 years old participated in the study. Participants completed demographics, the GDT, the Functional Gait Assessment (FGA), the Pediatric Vestibular Symptom Questionnaire (PVSQ), and the Pediatric Visually Induced Dizziness Questionnaire (PVID). Results: Children with concussion showed higher (worse) GDT scores (M=2.18 SD 1.93 seconds) than healthy controls (M=1.13 SD 0.95 seconds) that was statistically significant (P = 0.014). Conclusion: The GDT was able to distinguish between children with concussion and healthy controls. Given the simplicity of the GDT it can be used to help to discriminate children who have had a concussion.